The Form of Presentation and the Meaning of Giving Money in the art of Ranup Lampuan in Banda Aceh City - Utami, Intan Rizki Junita Tri (Universitas Ibn Khaldun, 2025)
Ranup Lampuan is an art form created specifically to maintain the customs and culture in Aceh. The dance reflects the customs of the Acehnese people, namely the peumulia custom. jamee . Peumulia jamie which is meant comes from the Acehnese language which means honoring guests. One form of honoring guests is by offering betel to the guests who are present. However, the giving of betel in this dance has shifted, namely when the dancer offers betel, the guest gives money to the dancer. This activity is a new phenomenon that has emerged in the Ranup dance The lights are called sawer. This attracts the author's attention to find out how the process of giving money emerged and why the giving of money, which is called sawer, appears in the Ranup dance. Lamp . In this study, the author uses the theory of symbolic interactionism in solving the formulation of problems that arise and to achieve answers to the formulation of the problem. This dance was created by Yuslizar in 1959. This study uses a qualitative method with a phenomenological approach. The results obtained from field is Ranup dance presentation form The lighting which consists of movement forms, accompanying music, floor patterns, costumes and properties as well as the phenomenon of giving money is still carried out today.